2008
DOI: 10.1016/j.janxdis.2007.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Autism spectrum traits in children and adolescents with obsessive-compulsive disorder (OCD)

Abstract: Objective: Assess the prevalence of autistic traits (AST) in pediatric OCD and relate them to OCD co-morbidity and compare them with published normative data.Methods: Pediatric patients with Obsessive-Compulsive Disorder (n=109) according to the DSM IV were studied using parent ratings of the Autistic Symptom/Syndrome Questionnaire to assess AST symptoms as a continuous rather than categorical trait. The KSADS, a semistructured psychiatric interview, was used for the psychiatric diagnostic evaluation. Also, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
60
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(70 citation statements)
references
References 31 publications
7
60
0
3
Order By: Relevance
“…These results might be related in both groups to the age and the level of development and concord with previous findings, which suggested the existence in childhood OCD of some impairments in perceiving, processing and describing repetitive thoughts and behaviours [12,27]. Also, the finding of no difference in insight amongst the two groups is in line with the study by Cath et al, which pointed out that egodystonicity did not discriminate between OCD and ASD subjects [9] and with the data of Ivarsson et al, who found in a paediatric OCD sample no relationship between the OCDpatients' level of insight and the presence of ASD traits [16].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results might be related in both groups to the age and the level of development and concord with previous findings, which suggested the existence in childhood OCD of some impairments in perceiving, processing and describing repetitive thoughts and behaviours [12,27]. Also, the finding of no difference in insight amongst the two groups is in line with the study by Cath et al, which pointed out that egodystonicity did not discriminate between OCD and ASD subjects [9] and with the data of Ivarsson et al, who found in a paediatric OCD sample no relationship between the OCDpatients' level of insight and the presence of ASD traits [16].…”
Section: Discussionsupporting
confidence: 88%
“…Higher prevalence of autistic traits has been found in OCD samples both in adults [5,6] and children [16], and some evidence suggests that treatments effective for OCD may be effective for repetitive thoughts and behaviours in ASD as well [15,19,24,25]. Also, family studies have reported an association between restrictive or repetitive behaviours in probands with autism and obsessive-compulsive features in parents both in multiplex [14] and sporadic autism families [1].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that these specific ASD domains may have a moderating effect on OCD severity. In contrast, Ivarrson and colleagues (Ivarsson and Melin, 2008), who investigated children and adolescents with OCD recruited from a Swedish hospital population, found that just roughly 9% showed symptoms of ASD. The study used a neuro psychiatric assessment supplemented by autism screening questionnaire covering current and preschool autistic symptoms completed by the parents.…”
Section: Main Text Introductionmentioning
confidence: 88%
“…Autism Spectrum Disorders ISSN: 2165-7890 AUO, an open access journal 'bizarre' behavior can induce a misdiagnosis of schizophrenia [11,[25][26][27]; a pattern of repetitive thoughts and behavior can lead to a misdiagnosis of obsessive disorder [28][29][30]; social withdrawal and difficulty in relationship with others can induce a misdiagnosis of social phobia [31] or schizoid/schizotypal personality disorder [32,33]; poor emotional control can cause a misdiagnosis of borderline personality disorder [34], and so on.…”
Section: Autismmentioning
confidence: 99%